2010
DOI: 10.1111/j.1445-5994.2008.01881.x
|View full text |Cite
|
Sign up to set email alerts
|

Higher peripheral neutrophil and monocyte counts are independent indicators of the presence and severity of proteinuria in apparently normal adults

Abstract: Our study showed that in apparently normal adults the presence and the severity of proteinuria could be reflected by the peripheral neutrophil and monocyte counts, but not the lymphocyte count. These findings, together with the documented inflammatory basis of proteinuria and the diverse pathophysiological roles of differential leucocytes, suggest that peripheral differential leucocyte counting may be useful in predicting the course of an existing proteinuria. Perspective longitudinal follow-up studies are nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…Nevertheless, neutrophils are also involved in numerous pathologies including tumors and tissue damage by forming neutrophil extracellular traps, secreting pro-inflammatory cytokines, releasing reactive oxygen species and damaging endothelial cells (5,6) . Consistently, previous cross-sectional studies have reported that the presence of proteinuria is significantly related to leucocyte and neutrophil counts (7)(8)(9)(10) . In addition, a prospective study has shown that elevated leucocyte counts were associated with an increased risk of proteinuria in Japanese men (11) .…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, neutrophils are also involved in numerous pathologies including tumors and tissue damage by forming neutrophil extracellular traps, secreting pro-inflammatory cytokines, releasing reactive oxygen species and damaging endothelial cells (5,6) . Consistently, previous cross-sectional studies have reported that the presence of proteinuria is significantly related to leucocyte and neutrophil counts (7)(8)(9)(10) . In addition, a prospective study has shown that elevated leucocyte counts were associated with an increased risk of proteinuria in Japanese men (11) .…”
supporting
confidence: 88%
“…Although there have been some previous cross-sectional studies that have reported inverse associations between leucocyte or neutrophil counts and proteinuria (7)(8)(9)(10) , crosssectional studies are not useful in determining temporal relations. A prospective study in Japanese men aged 40-55 years has shown that the highest quintile of leucocyte counts was associated with an increased risk of proteinuria incidence (hazard ratio 1•45, 95 % CI 1•23, 1•73) compared with the lowest quintile (11) .…”
Section: Discussionmentioning
confidence: 99%
“…year Follow-up months Definition of OA for inclusion Age, years Women, % No. of patients Quality score A B C D E F G H I J K L M Amin [ 10 ] 2009 30 ACR criteria 69 42 265 13 1 1 1 1 1 1 1 1 1 1 1 1 1 Tanamas [ 35 ] 2010 24 K/L 63.2 ± 10.3 51 109 13 1 1 1 1 1 1 1 1 1 1 1 1 1 Cicuttini [ 14 ] 2004 24 K/L 63.1 ± 10.3 58 113 12 1 1 1 1 1 1 0 1 1 1 1 1 1 Hill [ 19 ] 2007 30 ACR criteria 66.7 ± 9.2 41 233 12 1 1 1 1 1 1 0 1 1 1 …”
Section: Resultsmentioning
confidence: 99%
“…Roemer et al found an association in knees with more than two subregions with bone marrow lesions (BMLs), but no association when scoring BMLs [ 32 ]. Tanamas et al investigated the association for BMLs in the tibiofemoral joint [ 35 ]. They found significant associations for the total presence of BMLs and for medial BMLs.…”
Section: Resultsmentioning
confidence: 99%
“…In our study comparing PLR and NLR, there was no significant difference as a marker for proteinuria. Huang et al studied 12,225 normal healthy individuals who were called to hospital for checkup and found a significant relationship between total leukocytes, neutrophil, and monocyte counts and the presence of proteinuria but found no relation with lymphocyte counts .…”
Section: Discussionmentioning
confidence: 99%